Legislation in the field of renewable energy sources in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article the author analyzes the legislation in the field of renewable energy sources in the Republic of Kazakhstan. The main factor for the use of renewable energy sources in Kazakhstan, as well as throughout the world, is the need to reduce the negative impact of energy on the environment. Development of renewable energy sources in Kazakhstan are the provision of energy and environmental security, preservation of the environment, the conservation of its own energy resources for future generations.Key words: law, renewable energy, ecology, environment.